PENGARUH PENGENDALIAN INTERNAL DAN INTEGRITAS PADA KECENDERUNGAN KECURANGAN AKUNTANSI SATUAN KERJA PERANGKAT DAERAH KOTA DENPASAR - Kurnia Dewi, Kadek Yuli; Ratnadi, Ni Made Dwi (E-Jurnal Akuntansi; Vol 18 No 2 (2017), 2017)
This research aimed to get empirical evidence about the influence of internal controls and the integrity of the accounting fraud at SKPD tendency City Denpasar. The theory used in this study is the Attribution Theory and Fraud Triangle Theory. The population in this study were employees SKPD Denpasar. The samples used were 60 respondents to the sampling technique nonprobability sampling with purposive sampling. Collecting data using by questionnaires. The data analysis technique used in this research is multiple linear regression. The results of this research showed that the internal controls and the integrity of a negative effect of the accounting fraud at SKPD Denpasar.
Keywords: internal control, integrity, accounting fraud